Congenital nasal pyriform aperture stenosis in association with solitary median maxillary central incisor: unique radiologic features - Sara Yang, BS; Pedro Orta II BS; Elizabeth M. Renk, MD; Jared C. Inman, MD (Radiology Case Reports, 2016)
Solitary median maxillary central incisor (SMMCI) coexists in 34%-65% of patients initially diagnosed with congenital nasal pyriform aperture stenosis. SMMCI, a genetic syndrome, warrants consideration for further screening because of its high prevalence of other diagnostic possibilities—specifically central defects, like nasal obstruction and hypothalamo-pituitary axis abnormalities. We report on a presentation of SMMCI with congenital nasal pyriform aperture stenosis which highlights the unique radiologic features and notes the relationship between these two central associated findings in the literature.